Responsible Corporate Behaviors: Drivers of Corporate Responsibility - Tan, Basak Ucanok (Igi Global, 2017)
The aim of this chapter is to outline the growing interest on corporate responsibility, how it has evolved and transpired itself in the form of CSR. In this respect the chapter begins by reviewing the definitions of corporate responsibility and emphasizing its difference from related concepts. In the following section major cornerstones in the evolution of corporate responsibility are explained along with a brief outlook of how the modern approaches to corporate responsibility have changed in the past 30 years. The main focus of the chapter is on factors that shape corporate responsibility. In this respect attention is directed to four perspectives used in organization studies; economic, institutional, cultural and cognitive. Theoretical underpinnings, empirical research and examples are provided for the drivers of corporate responsibility. The chapter demonstrates benefits of integrating multiple perspectives and discusses directions for the future of corporate responsibility.
Keywords: Social-Responsibility; Financial Performance; Leadership; Perspectives; Initiatives; Citizenship; Management; Companies; Business; Strategy